Controlling Rice Pests with Biopesticides: Counseling at BPP Nusa Bakti, Belitang III District, East OKU - Haperidah Nunilahwati; Yani Purwanti; Neni Marlina; Laili Nisfuriah; Marlina Marlina; Asmawati Asmawati; Fitri Yetty Zairani; Burlian Hasani; Ira Indrayani (Altifani Journal: International Journal of Community Engagement, 2023)
Counseling activities on the use of biopesticides in controlling pests in rice cultivation in the target area of BPP Nusa Bakti, Belitang III District, OKU Timur Regency have been carried out successfully. The aim of the extension activities is to increase understanding of biopesticides and their use as an alternative solution that is environmentally friendly in controlling pest attacks on rice plants. Implementation of activities from January 25 to February 17 2022 with participants from the Nusa Bakti assisted area group. The methods used are counseling (submission of materials and discussions), demonstrations (application of biopesticide) and evaluation. The results of this extension activity showed a positive response and farmer enthusiasm, increased knowledge about biopesticides, and was considered to provide an environmentally friendly influence in controlling rice plant pests.